Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1510/icvts.2010.257568
|View full text |Cite
|
Sign up to set email alerts
|

Can leucocyte depletion reduce reperfusion injury following cardiopulmonary bypass?

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'Can leucocyte depletion (LD) reduce reperfusion injury following cardiopulmonary bypass?'. Altogether more than 74 papers were found using the reported search, of which nine represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Short-term use of a leukocyte filter reduced circulating leukocytes; with continued usage, leukocytes that adhered to the filter membrane disrupted, leading to leakage of protease, inflammatory reaction, and tissue destruction. Our results may explain why leukocyte depletion could not improve the outcomes in some clinical studies [1214]. …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Short-term use of a leukocyte filter reduced circulating leukocytes; with continued usage, leukocytes that adhered to the filter membrane disrupted, leading to leakage of protease, inflammatory reaction, and tissue destruction. Our results may explain why leukocyte depletion could not improve the outcomes in some clinical studies [1214]. …”
Section: Discussionmentioning
confidence: 83%
“…Some studies have suggested that leukocyte filters could reduce expression of CD11b/CD18 in leukocytes [6], alleviate systemic inflammatory responses [7, 8], and improve outcomes [7, 9, 10]. However, other studies have shown that leukocyte filters cannot reduce [11], and may even increase, the release of inflammatory cytokines and proteases, and thus could have a negative effect [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…another study showed that leukocyte removal by filters is suitable and safe for use during cardiac surgery. early clinical reports appeared to confirm these findings, but reviews in recent years have concluded that the clinical effects have not been evaluated vigorously enough and that no recommendations can be made regarding the use of leukocyte-depleting filters in routine cardiac surgery 8 . The aim of this experimental study was to prevent sirs by reducing all blood components of the host protection system (plasma protein systems, leukocytes and thrombocytes) by using pre-operative aphaeretic-filtration in a pig model of sirs elicited by cpB, with 4 days of postoperative observation.…”
Section: Introductionmentioning
confidence: 99%
“…There are pharmacologic tools, and protective processes, which can reduce IR injury. Antioxidants, such as N-acetylcysteine, vitamin E, mannitol, thiols, alkaloids and endogenous antioxidants, such as superoxide dismutase, reduced glutathion, glutathione reductase, catalase, or ion chelators functions due to inactivation of free radicals, which are key element in IR induced tissue damages (Arato et al 2010), (Peto K, et al 2007 ), but leukocyte depletion, anti-cytokine or leukocyte adhesion molecule monoclonal antibody therapies ended with conflicting results (Arato et al 2010) (Loberg AG et al ,2011). Among other effective possibilities, ischemic postconditioning is one of the most effective processes in reducing IR caused damages, which was first introduced by Vinten-Johansen's group in 2003.…”
mentioning
confidence: 99%